Taxonomy of alkalophilic Bacillus strains by analysing the nucleotide sequence of the 16S-RNA gene - Chinh, Tang Thi (Academia Journal of Biology, 2006)
Two alkalophilic Bacillus strains HA401 and IBT012, which produced alkaline a-amylase, were isolated from the Catba and Haiphong sea sides. The identification by classical method showed that they belonged to the genus Bacillus. The nucleotide sequence of the 16S-RNA gene of these two strains showed that the one of the strain Bacillus IBT012 had 98% homology with the one of the strain Bacillus subtilis 2633 and the one of the strain Bacillus HA401 had 97% homology with the one of the strain Bacillus subtilis 2633. Therefore, these two isolated strains belonged to the species Bacillus subtilis. The nucleotide sequence of the16S-RNA gene of the strain Bacillus HA401 was submited to the NCBI genbank database with the genbank accession number: AY279207.